Cereal Market before and after the Integration of Poland into the European Union. Dynamics of Supply and Demand Correlations = Rynek zbóż przed i po integracji Polski z Unią Europejską. Dynamika relacji popytowo-podażowych - Czakowski, Dariusz (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this publication is to show some changes in supply and demand correlations on the cereal market after Poland?s accession into the European Union. To meet the above objective there were compared some data concerning the volume of domestic cereal production and its cereal species structure, foreign trade balance, domestic consumption and purchase price levels. The formation of the above mentioned items was analyzed for two periods.
Keywords: gospodarka żywnościowa; rynki rolne; rolnictwo; rynek zbóż; integracja europejska; food economy; agricultural markets; farming; cereal market; European integration